War, blockades, and hunger: nutritional deprivation of German children 1914-1924 - Cox, M (University of Oxford, 2013)
At the beginning of the First World War, the British imposed a blockade against Germany intending to prevent all imports from entering the country. Germans began to call the British naval action the Hungerblockade, claiming that it seriously damaged the well-being of those on the home front, namely women and children, through lack of adequate nutrition. These German claims that Britain used hunger as a weapon of war against civilians have sometimes been dismissed as propaganda. However, newly discovered anthropometric measurements made of German school children during the war gives credence to German contentions that the blockade inflicted severe deprivation on children and other non-combatants. Further, these data show that the blockade exacerbated existing nutritional inequalities between children of different social classes; working class children suffered the most profound effects of nutritional deprivation during the war. Once the blockade ended however, working class children were the quickest to recover, regaining their pre-War standards in weight by 1921. They surpassed their own pre-War height standards by 1923, and approximated the weight of middle class children by 1924. This recovery of working class children is likely due to the outpouring of international aid targeted at poor German children. These data also indicate significant gender inequalities starting at age fourteen in nutritional status, with male adolescents suffering far greater deprivation from 1914-1924.